Correction of severe upper-eyelid sunken deformity in Asians by double-eyelid procedure and combination of orbital fat pad repositioning and autologous fat transplantation: a one-year follow-up study of 79 cases - Shen, Haiyan; Zhang, Jufang; Tan, Weiqiang; Cai, Xiujun (Frontiers in Surgery, 2024)
Correction of severe upper-eyelid sunken deformity in asians by double-eyelid procedure and combination of orbital fat pad repositioning and autologous fat transplantation: A Oneyear follow-up study of 79 cases Background：Nowadays,people's pace of life continues to rapid up, and many bad habits will accelerate the aging of the eye periphery, and patients with sunken upper eyelids are to be found in younger people. In young Asians, single eyelids are often accompanied by upper eyelid depression, so correcting the upper eyelid depression during blepharoplasty becomes a higher challenge for plastic surgeons. Current surgical methods for upper eyelid depression include three major categories: tissue repositioning, injection and filling, and combined use. According to [1], grades 1 and 2 are mild or moderate upper eyelid sunken. The sunken can be well corrected only by repositioning the orbital fat pad, while the correction effect for severe upper eyelid sunken in grades 3 and 4 is Poor, need to be used in combination to achieve the desired effect.Purpose: The authors sought to determine whether, for patients with single eyelids and severe upper eyelid depression of grades 3 and 4, combined with orbital fat pad repositioning and autologous fat transplantation during blepharoplasty, an aesthetic and youthful blepharoplasty can be achieved. Methods: This study included 79 patients with single eyelids and severe upper eyelid depression of grades 3 and 4 who received treatment between June 2020 and July 2022. All patients underwent double eyelid surgery plus orbital fat repositioning and autologous fat grafting. Results: After a minimum follow-up period of 1 year, overall patient satisfaction was 92%. The recurrence rate within the first year was 6% and the complication rate was 5%. Conclusion: This combined surgery may be an option for young Asians with single eyelids and severe upper eyelid depression. In this study, the surgery resulted in natural-looking double eyelids and younger-looking eye sockets in most patients. A combination of different surgical methods based on the patient's preoperative condition is critical to achieving long-term correction.